Linear and flat antenna arrays focused on a broadband signals in radio communications, microwave technologies and non-destructive testing - Denis A. Vedenkin (Физика волновых процессов и радиотехнические системы)
Background. The main properties and characteristics of focused antenna systems using narrowband signals are known and generally coincide with the properties of broadband discrete antennas with a symmetric spectrum. The use of broadband signals allows expanding the technical capabilities of devices using focused electromagnetic fields. This article is devoted to assessing the properties of broadband focused fields formed by signals with both continuous and discrete spectrums, and the possibility of creating special spatial distributions of focused fields is shown. An approach to the synthesis of broadband focused antenna arrays is proposed. A number of technical applications of antenna arrays focused in the near-field zone by a broadband signal have been developed. The aim of this article is to describe the main properties of focused broadband electromagnetic fields, to demonstrate the possibility of forming special focused spatial distributions and to develop practical application options based on them. Methods. Achieving the goal of the article is due to the use of well-known principles of electrodynamics and aperture theory of antennas. Results. The features of the formation of focused broadband electromagnetic fields are shown and their main properties are given. Options for the technical application of focused broadband antennas in radio communication and direction finding tasks are proposed. Conclusion. The results obtained confirm the importance of assessing the properties of broadband focused antennas and developing a number of technical proposals based on them.